TENSILE STRENGTH PROPERTIES OF POLYETHYLENE NETTING TWINES UNDER EXPOSURE TO OUT-DOOR AND ARTIFICIAL UV RADIATION - MEENAKUMARI, B; RAVINDRAN, K (Fishery Technology, 2017)
Photodegradation of three types of polyethylene twines namely, polyethylene fibrillated tape twine, polyethylene flat tape twine and polyethylene monofilament twines were studied by exposing them to sunlight and a rtificial UV radiation. The percentage residual strength varied in the samples, the monofilament with the highest residual strength followed by :fibrillated tape twine and flat tape twine. A plot of the difference between the breaking strengths of the :fibnUated tape twine and the mono: filament twines against any given period of exposure exhibited a linear relationship.